The Effect of Suplementation Omega-3 on Sputum Conversion, Body Mass Index, Interleukin-6 and Monocyte Lymphocyte Ratio in the Treatment of Pulmonary Tuberculosis - Ferryansyah, Ferryansyah; Isa, Mohamad; Juhairina, Juhairina; Haryati, Haryati; Assagaf, Ali; Kusumawardhani, Erna (Newinera Publisher, 2025)
Tuberculosis (TB) is a disease caused by Mycobacteriun Tuberculosis. Its cases continue to increase both in Indonesia, and in the world. Efforts to increase the success rate of TB treatment and reduce the level of transmission need to continue to be developed, one of which is with additional therapy in its treatment. Omega-3 has anti-inflammatory and anti-bacterial potential, which is predicted to increase the success of TB treatment, as seen from sputum conversion, increased body mass index (BMI) and important inflammatory parameters in TB infection namely interleukin-6 (IL-6), monocyte lymphocyte ratio (MLR) values. This study was conducted to determine the effect of Omega-3 addition on sputum conversion, BMI, IL-6 levels and MLR values in pulmonary tuberculosis treatment. Experimental study with consecutive sampling in drug-sensitive pulmonary TB patients who were given additional Omega-3 dose of 1,200 mg (@600mg/capsule), compared with the control group. Each sample was monitored for sputum conversion, BMI, IL-6 levels and MLR values at week 0 (m0), week 4 (m4) and week 8 (m8). In this study, there was a significant effect of adding Omega-3 on reducing IL-6 levels (p= 0.013), reducing MLR values (p= 0.005) and increasing BMI (p= 0.047) but no significant effect on sputum conversion (p= 1,000). The addition of Omega-3 had a significant effect on reducing IL-6 levels, reducing MLR values and increasing BMI, but did not have a significant effect on sputum conversion in pulmonary TB treatment.